Bireysel bankacılıkta kredi kartları - Ispartalı, Mehmet (My University, 2001)
Kredi kartları bugün bankaların en önemli bireysel bankacılık ürünlerinin başında gelmektedir. Bankalar açısından bakıldığında üye işyerlerinden sağladıkları komisyonlar, ayrıca müşterilerden tahsil ettikleri faizler ve kart ücretleri, kart sahipleri açısından bakıldığında ise nakit para taşımaksızın sadece bir kart ile alışveriş yapabilmeleri , nakit paraları olmamasına rağmen banka ATM'lerinden nakit çekme imkanları olması, aynı zamanda yapmış oldukları bir alışverişi kredi kartı son ödeme tarihine kadar bankanın fonlaması ve sonucunda da faiz ödenmemesi kolaylıkları sonucunda kredi kartı her iki taraf için de cazip hale gelmiştir. Daha önceleri para bir mübadele aracı olarak tanımlanırken; kısa bir süre sonra kredi kartlarının paranın yerini almasıyla birlikte, kredi kartları için mübadele aracı tanımlaması kullanılabilecektir.. Teknolojik gelişmelerden biri olan, belki de çağımızın en büyük keşfi olarak niteledirilebilecek internet ile birlikte kredi kartı uygulamasında bir yenilik daha gündeme gelmiştir. İnternet sayesinde insanlar gerek evlerindeki, gerekse işyerlerindeki PC'lerinden bankalarına ulaşıp; tüm kredi kart detay bilgilerine sahip olup, ayrıca tüm ödemelerini de kredi kartı ile gerçekleştirebilmektedirler. Bankalar ticari faaliyetlerinin bir gereği olarak; ağırlıklı olarak şimdiye kadar ticari işlemlere ağırlık vermelerine rağmen, Türkiye'de kısa sürede bankaların bile beklemedeiği bir talep patlaması sonucunda, Türk toplumunun kredi kartına yoğun ilgi göstermesiyle; riski tabana yayma suretiyle, bireysel müşterilere kredilendirilme imkanı vermiştir. Kredi kartının Türkiye'de ilk çıktığı yıllarda; bankalara kredi kartı vermek için oldukça seçici davranırken; şu anki ortamda hemen hemen tüm bankalar kefil uygulamasını da ortadan kaldırarak, kişilerin gelirini beyan etmesi suretiyle, sorunlu mali geçmişi olmayan kişilere kredi kartı vermektedirler. Ayrıca; eskiden insanlar kredi kartı almak için banka kapılarında bekleyip, büyük uğraşlar sonunda kredi kartı sahibi olurken; günümüzde bankalar eski stratejilerin değiştirmiş, kampanyalar ve direk satışlar düzenlemek suretiyle; müşterileri ofislerinde ziyaret etmek suretiyle kart vermeye başlamışlardır. Hatta kredi kartı veren hemen her banka çeşitli promosyonlar düzenlemek suretiyle, kart verilmesini cazip hale getirmeye ve bu şekilde müşterilerini ikna etmeye çalışmaktadırlar. Puan Kataloğu aracılığıyla hediye uygulaması, yapılan alışverişlerde müşterinin havayollarından bedava mil kazanması, bazı mağazalarda özel indirimler uygulanması, bankasından kart alana hayat sigortası yapılması belli başlı uygulamalar arasında sayılabilir.

The latest developments in financial markets forced banking sector to lean towards instruments that can provide more profit apart from the present services due to such reasons as shrinking of profit margins and expectation for the fall in therate of inflation. The extent of the competition in the sector of individual banking can be better observed in the product diversity, variety in services, assurance of maximum customer satisfaction, introduction of new products into the individual banking sector and rendering customized banking services. In this competition, credit cards have turned into a product, which we can define as the hook product, since they are expected to draw customers' investments into the bank in the future. Credit cards have easily been adopted by Turkish people in a short period of time and banks gained much more credit card customers than they ever expected because they enable cardholders to do shopping without any cash payments and it is very similar to the installed payment system with which Turkish people are well familiar. Credit cards are one of the leading individual banking products today. Credit cards have become advantageous for both parties; when considered from banks' point of view, they are advantageous due to the commissions provided by the members and the interests and card rates collected from the cardholders, and when viewed from the card holders point of view they are still advantageous for enabling them to do shopping with only one card without keeping any cash and to draw cash through ATMs when they need. Another advantage of a creditcard for cardholders is that banks fund a shopping they do until the date of payment and no interest is charged if the payment is effected within the given period. While money was being defined as a means of exchange before, the definition of means of exchange can well be used for credit cards with the replacement of money with credit cards in a short period of time. Another innovation was brought up in the application of credit cards with the introduction of internet, one of the technological developments that can be described as the greatest discovery of our age. Human beings can have access to their banks over the PCs at home and offices, they can see all the details about their credit card and besides they are able to effect their payments through credit cards. In spite of the fact that banks gave priority to commercial transactions more so far, individual customers were given the opportunity of credibility by spreading the risk to the base when Turkish society showed a great interest to credit cards as a result of an unexpected explosion of demand that took place in a short period of time. While the banks were very selective in the issuance of credit card during the first years credit cards were introduced in Turkey, now almost all banks have already given up requesting a guarantor from a credit card customer and started to issue credit cards to anybody with no troubled financial background on condition that they give a financial statement. Moreover, while individuals used to have a credit card after great efforts and long waits in front of the bank, now banks have changed their strategies and have started to give cards by way of visiting customers at their offices and organizing campaigns and direct sales. Nearly all banks that give credit cards are trying to render the issuance of cards attractive and thus persuade their customers through organizing various promotions. Among major promotional applications are gifts through bonus catalogues, free flight tickets from the airlines inreturn for their shopping, special discounts in certain stores and issuing life insurance for those obtaining credit cards from their banks. Credit Cards are plastic payment tools that provide consumers with payment flexibility. These cards can be used internationally to make purchases and withdraw cash. At the end of every month, the consumer can decide whether to payy of the entire balance without incurring any interest charges -or- pay a portion of the total balance, and then pay in terest on the balance deferred. Banking industry specialists also consider credit cards to be the most attractive consumer-banking product. Why? Credit cards offer banks: ·Interchange revenue ·Fee revenue ·Interest revenue Europen banks and customers have a well deserved reputation for being risk and debt averse. Taditonally; Continental European banks have offered their customer credit cards that really function as deferred debit cards,. Historically, European banks cooperated with each other in terms of credit card processing. In many of the large European markets, many of the big banks own a national card processing company. These card processing companies treat credit cards as a commodity and have significant restrictions on what product features can be offered in a given market. As a result; Banks that participate in these processing agreements are not able to differentiate their product from their competitors. While in the past European banks were fairly satisfied with status quo, there are indications that this is changing. The factors that are driving this change are: ·In Europe, the fastest growing credit card issuers are non-bank players who have traditionally worked in the private label market. These consumer finance houses are beginning to develop their own national acceptance networks for credit cards and ate applying for international acceptance branding. In short, the growth and profit of the consumer finance houses are coming at the direct expense of the consumer banking industry. European banks still have significant advantages in the credit market. Two important ones are; ·Brand allegiance - consumers still tend to choose a bank in their home country. ·Customers databases -in order to be sucessful, credit card issuers must have access to large customers databases that include credit history. Due to the absence of traditional white data credit bureaus and consumer privacy laws, the existing European banks have a monopoly in this area. When considering launching a credit card product to your existing customer base, you must carefully examine what the policy will be if the customer already has a bank-issued credit card. The reality of the Continental European marketplace is that many banks hve already issued credit cardsto their customers. However, this cards require payment-in-full at the end of the month, which the industry usually refers to as charge cards. While you can not tell the difference between a charge card and credit card by looking at them -they are very different in functionally and profit. Charge cards do not offer the customer the financial flexibility of paying in full or spreading payments over a period of months. Charge cards also do not produce interest revenue for banks. If you decide to issue the credit card in addition to the existing charge card, it is unlikely that the customer will want to pay an annual fee on both cards. In this instance, the revolving credit card should be promoted as having no annual fee- or - waive the fee for the first year. If possible, have a credit bureau screen your revolving credit candidates to make sure they have not had any previous credit problems. PRODUCT PROPOSITION Product features can be tailored and competitively adjusted to meet the needs of a target marke. Once the target market has been defined, product features that would be of percieved value to that target market should be identified. For instance, if the target market is for new parents they may be much more interested in points programs or coupons for infant products than in access to airline lounges. The list of credit card product features used to differentiate credit card offerings is expanding constantly. Credit product features include; ·Interest rates, ·Annual fees, ·Second card for spouse partner ·Size of credit line ·Cash advance Access ·Color of card (standart, gold, platinum, etc.) ·Co-brands, ·Affinity Programs, ·Reward Programs, ·Discounts, ·Credit insurance, ·Purchase Protection Insurance ·Float Periods (Interest Grace Periods) ·Global Acceptance, ·Travel Protection Insurance, ·Photo Card ·Fraud Protection ·Membership Subcriptions ·Access to Airline Lounges All credit card programs do not include all of above mentioned features. In markets that are new to credit, the product is usually fairly generic and the features are limited. Once the market has become more established, these features are used very competitively. In the markets that are close to saturation, interest rates are used to attract new cardholders. It should be noted that customers that apply solely on the basis of a low interest rate are more likely to close their account (i.e.,attrite) when offered a still cheaper interest rate by a competitor. ACQUSITION CHANNELS Credit is usually offered to consumers using one of the following acqusition channels: ·Existing Bank Customer cross-sells, ·Direct Sales ·Telemarketing ·Direct Mail ·Take Ones ·Bind-Ins ·Affinity Programs, ·Co-brands ·Internet ·Member-get-member ·Branch-based Sales İncentives ·Portfolio Purchase CO-BRANDING Co-branding is an association of persons who share risk and profits in a juint venture. A strategic partnership between a card issuer and a commercial partner who has: -Own distrubition -Recognised strong brand in a specific sector -Profit objectives Co-branded programme takes place when the two organisations combine to: -Market a specialised card to the commercial partner's customer base, -And non-customers The Benefits of Co-branding Because when two, or more, entities get together to combine their strenghts and skills they can deliver a product and service to consumers which is better then either could do on its own. -Additional revenue stream, -Product differentiation, -Access new customers with new delivery, -Gain access to specialists skills that banks do not have or cannot develop, -Potential for cross selling, -Improved customers loyalty relationship, -Differentation in crowded market, CARDHOLDER BENEFITS -Combined brand strength, -Purchase discounts, -Frequent buyer programs, -Free merchandise, -Special services, -Loyalty, -Billboard on the wallet ISSUER BENEFITS -Lower acqusitions and marketing costs, -Product differentation & pricing opportunities, -Customer loyalty, -Incremental revenue from from new card volume & fees, -Cross-selling opportinites, -Financial liability for cardholders, -Possibility of revenue sharing,
Keywords: Bankacılık-kredi Kartları; Ekonomi; Finansman ekonomisi; Kredi; Kredi kartları; Kredi Kartları Türkiye